Towards Goal-oriented Process Mining - Ghasemi, Mahdi (Université d'Ottawa | University of Ottawa, 2018)
The growth of our digital world makes it possible to record many types of events. In particular, the number of business processes whose events are being logged is significantly increasing. Process mining is an approach that exploits event logs to discover real processes executed in organizations, enabling them to (re)design and improve process models. Goal modeling, on the other hand, is a requirements engineering approach mainly used to analyze what-if situations and support decision making. Common problems with process mining include the complexity of discovered “spaghetti” processes and a lack of goal-process alignment. Current process mining practices are mainly oriented towards activities and do not profit from considering stakeholder goals and requirements to manage complexity and alignment. Involving goal-related factors can augment the precision and interpretability of mined models and lead to better opportunities to satisfy stakeholders. In this research, I propose two methods (for goal-oriented process and enhancement discovery, and for conformance checking) that show potentially synergetic effects achievable by combining process mining and goal-oriented modeling. The paper reports on the research method, the gap/problems being addressed, preliminary solutions, expected contributions, and main foreseen challenges.
Keywords: Process Mining; Data-Driven; Goal Modeling; Business Process Management; Requirements Engineering; Event Logs; Goal Mining